Guillain–Barré Syndrome Variant Occurring after SARS‐CoV‐2 Vaccination. Issue 2 (2nd July 2021) - Allen, Christopher Martin; Ramsamy, Shelby; Tarr, Alexander William; Tighe, Patrick Jason; Irving, William Lucien; Tanasescu, Radu; Evans, Jonathan Rhys
Abstract : Although SARS‐CoV‐2 vaccines are very safe, we report 4 cases of the bifacial weakness with paresthesias variant of Guillain–Barré syndrome (GBS) occurring within 3 weeks of vaccination with the Oxford–AstraZeneca SARS‐CoV‐2 vaccine. This rare neurological syndrome has previously been reported in association with SARS‐CoV‐2 infection itself. Our cases were given either intravenous immunoglobulin, oral steroids, or no treatment. We suggest vigilance for cases of bifacial weakness with paresthesias variant GBS following vaccination for SARS‐CoV‐2 and that postvaccination surveillance programs ensure robust data capture of this outcome, to assess for causality. ANN NEUROL 2021;90:315–318